Investigation of electromyography of the masseter and temporal muscles in children with Down syndrome aged 2 to 12 years during maximal voluntary isometric contraction and rest - Abdol Reza Yavari; Mahdi Panahian; Hossein Soltaninejad; Mohamad Reza Arab; Marzieh Babaei (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2024)
Background. Muscle weakness and low muscle tone may cause chewing and swallowing disorders in people with Down syndrome. This study investigated the electromyography of the masseter and temporal muscles in children with Down syndrome, aged 2 to 12, during maximal voluntary isometric contraction and rest. Methods. The current descriptive-analytical and case-control study investigated the electromyography frequency indicators of the masseter and temporal muscles at maximum voluntary contraction and resting states in 15 children aged 2 to 12 with Down syndrome and 15 normal children of the same age. Results. The average frequency of the mean and median in the electrical signal of the masseter and temporal muscles on the left and right sides and in two different positions in children with Down syndrome is lower than in normal children. In comparing the average frequency of the mean, except for the left and right temporal muscles in the maximum voluntary isometric contraction and the left master muscle during rest, there is a significant difference in the rest. Also, in comparing the average frequency of the median, except for the left and right temporal muscles in the resting state, there are non-significant differences in the rest of the cases. Conclusion. The average frequency of the electrical signal of the masseter and temporal muscles in children with Down syndrome is lower than that of normal children. Unlike typically developing children, those with Down syndrome struggle with chewing and swallowing. Practical Implications. The data obtained from this study contributes to the enhancement of interventions and treatments for patients with Down syndrome.